Kesalahan Penerjemahan Google Translate Pada Hadis Arbain Berdasarkan Konteks Keagamaan (Kajian Akar Kata dan Morfologi Turunan) - Agustian Rahmadi (Alsina : Journal of Arabic Studies, 2022)
Translation is the activity producing a source language message with the closest and natural equivalent to the recipient's language, both in terms of meaning and style. The translation process requires grammatical and lexical adjustments to evade unusual structures in the recipient's language. Translation activities are not only done by humans. With the advancement of technology, electronic translation tools have emerged such as Google Translate to translate parts of text or web pages from one language to another. This study aims to describe the Google Translate system in translating a Hadith Arbain text and to analyze the forms of translation errors in the study of root words and derived morphology. This research is a qualitative descriptive study with the source of data and the object is the translation of the Google translation and the Hadith Arbain. Data collection is done by documentation. Error analysis is used in conducting data analysis of translation errors to find errors in the meaning of Arabic morphology forms against Indonesian and vice versa, grammatical errors, meaning of the same root words but different sounds, meaning of glorification, classifying words of the original language into the target language, the use of inappropriate target words, translation, and the meaning of Islamic concepts.